Rare familial TSC2 gene mutation associated with atypical phenotype presentation of Tuberous Sclerosis Complex. Issue 3 (27th January 2017) - Fox, Jonah; Ben‐Shachar, Shay; Uliel, Shimrit; Svirsky, Ran; Saitsu, Hirotomo; Matsumoto, Naomichi; Fattal‐Valevski, Aviva
Abstract : Tuberous sclerosis complex (TSC) is a neurocutaneous disorder that results from mutations within either the TSC1 gene or the TSC2 gene. Diagnosis is based on well‐established clinical criteria or genetic criteria. We describe an 18‐month‐old boy who presented with seizures and a single hypopigmented macule. He did not meet consensus criteria for the clinical diagnosis of TSC. Exome sequencing revealed a heterozygous TSC2 mutation (c.5138G>A (p.Arg1713His)) in the patient. This heterozygous alteration was detected in his mother as well as several other maternal family members. The mother and other family members with the mutation were asymptomatic except for the presence of hypopigmented macules. The phenotypic characteristics of the individuals in this family were not suggestive of a TSC2 mutation as none satisfied the clinical criteria for even a diagnosis of possible TSC. This case provides evidence for a unique TSC2 mutation that resulted in an atypical clinical presentation and indicates potential shortcomings of the current diagnostic criteria for TSC. These findings may have implications for genetic counseling and screening. © 2017 Wiley Periodicals, Inc.